1989
DOI: 10.1021/bi00430a013
|View full text |Cite
|
Sign up to set email alerts
|

Multiple conformational states in myoglobin revealed by frequency domain fluorometry

Abstract: The tryptophanyl fluorescence decays of two myoglobins, i.e., sperm whale and tuna myoglobin, have been examined in the frequency domain with an apparatus which utilizes the harmonic content of a mode-locked laser. Data analysis was performed in terms of continuous distribution of lifetime having a Lorentzian shape. Data relative to sperm whale myoglobin, which possesses two tryptophanyl residues, i.e.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 35 publications
2
13
1
Order By: Relevance
“…It is worthy of note that the corrected fractional increase observed for wild-type apomyoglobin is practically coincident with the sum of the yield increases of the protein mutants containing a single tryptophanyl residue. The fractional increase determined for the complex between ANS and tuna apomyoglobin, a protein that contains a single tryptophan at position 14 (12,28,29), was 0.680, a value similar to that found for the sperm whale mutant containing only W14. The fractional increase exceeding that of the reference mutant depends on the transfer efficiency Q T and on the ratio between the absorption coefficients of the donor at 295 nm and acceptor at 350 nm, i.e.…”
Section: Resultssupporting
confidence: 75%
“…It is worthy of note that the corrected fractional increase observed for wild-type apomyoglobin is practically coincident with the sum of the yield increases of the protein mutants containing a single tryptophanyl residue. The fractional increase determined for the complex between ANS and tuna apomyoglobin, a protein that contains a single tryptophan at position 14 (12,28,29), was 0.680, a value similar to that found for the sperm whale mutant containing only W14. The fractional increase exceeding that of the reference mutant depends on the transfer efficiency Q T and on the ratio between the absorption coefficients of the donor at 295 nm and acceptor at 350 nm, i.e.…”
Section: Resultssupporting
confidence: 75%
“…It is worthy of note that the corrected fractional increase observed for wild‐type apomyoglobin is practically coincident with the sum of the yield increases of the protein mutants containing a single tryptophanyl residue. The fractional increase determined for the complex between ANS and tuna apomyoglobin, a protein that contains a single tryptophan at position 14 (12,28,29), was 0.680, a value similar to that found for the sperm whale mutant containing only W14. The fractional increase exceeding that of the reference mutant depends on the transfer efficiency Q T and on the ratio between the absorption coefficients of the donor at 295 nm and acceptor at 350 nm, i.e.…”
Section: Resultssupporting
confidence: 69%
“…The emission decay of intrinsic or extrinsic fluorophores bound to apomyoglobin is dependent on the number of such subconformations as well as on the interconversion rate among these substates. Recent studies demonstrated that the tryptophanyl fluorescence emission of apomyoglobin as well as that of 2,6-p-toluidinenaphthalene sulfonate bound to the heme pocket of the apoprotein can be represented by a quasi continuous-lifetime distribution Bismuto et al, 1989a;1989b). More recently, it was shown that the tryptophanyl fluorescence decays of fully unfolded polypeptides are characterized by broader lifetime distributions whose width at half maximum is logarithmically related to the polypeptide chain length (Bismuto et al, 1991).…”
mentioning
confidence: 99%